Lexical organization in deaf children who use British Sign Language: Evidence from a semantic fluency task*. Issue 1 (2nd May 2012) - MARSHALL, CHLOE R.; ROWLEY, KATHERINE; MASON, KATHRYN; HERMAN, ROSALIND; MORGAN, GARY
ABSTRACT: We adapted the semantic fluency task into British Sign Language (BSL). In Study 1, we present data from twenty-two deaf signers aged four to fifteen. We show that the same 'cognitive signatures' that characterize this task in spoken languages are also present in deaf children, for example, the semantic clustering of responses. In Study 2, we present data from thirteen deaf children with Specific Language Impairment (SLI) in BSL, in comparison to a subset of children from Study 1 matched for age and BSL exposure. The two groups' results were comparable in most respects. However, the group with SLI made occasional word-finding errors and gave fewer responses in the first 15 seconds. We conclude that deaf children with SLI do not differ from their controls in terms of the semantic organization of the BSL lexicon, but that they access signs less efficiently.